Diaspore bank of aquatic macrophytes maintaining species diversity in a Neotropical pond - Ferreira, Fernando Alves; Catian, Gisele; Pott, Arnildo (Acta Scientiarum. Biological Sciences, 2016)
The diaspore bank is an important component of biological diversity acting mainly as storage and source of diaspores, which also indicate dynamics and patterns of maintenance of plant diversity. We tested the hypothesis that the diaspore bank would be the responsible factor for the maintenance of the aquatic plant species, used two techniques to evaluate the diaspore bank: seedling emergence and direct counting of field samples. Density and richness of the diaspore bank were correlated with plant cover of the aquatic macrophyte communities and also with the euphotic zone radiation in different phases of the hydrological cycle. The diaspore bank is a key factor in maintenance of aquatic macrophyte assemblages in this pond. Nymphaea amazonum was one of the dominant species in the pond and presented temporally peaks of plant cover. Furthermore, depth allowed induction of germination of stored diaspores. Therefore, the diaspore bank may predict which species colonizes a site when environmental characteristics are favorable and allows inferring which processes are linked to changes in structure of aquatic macrophyte assemblages. These mechanisms are the means for recovery of macrophyte species under natural disturbances, represented by water level oscillations in floodplains.